PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM-ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR GEOGRAFI - Nuryati, Sri; Rosnita, Rosnita; Christanto, Ludovicus Hari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to analize the different of applying cooperative learning student team achievement type and not appliying that to disaster management for learning outcomes of the XI grade students in SMA N 2 Pontianak and also to analize the effect of applying that. The research method is descript quantitative. The subject of this experiment is student of XI grade with total 160 students and the data can record from learning outcomes that is numeral data from disaster menegement learning. The plan that used in this experiment is experiment with quasy experiment with nonequivalent control group design that consist of three step is preparation step with observation, prepare the instrumen, realization step with applying cooperative learning student team achievement type and fnish step with analize the learning outcomes of the students and make the report. The average learning outcomes of post-test class experiment is 79,25 and class control is 71,38 gained t_arithmetic is 4,343 and t_table ? = 5% is 2,023. So, t_arithmetic (4,089) > t_table (1,999). Then , Ha is accepted. It can be conclude that there is the effect of applying cooperative learning type student team-achievement division to the learning outcome of XI grade students in SMA N 2 Pontianak. Therefore, the effect size is 0,511(medium criteria). It means that learning by applying cooperative learning type student team-achievement division to hydrosphere gives effect to the XI grade students in SMA N Pontianak learning outcomes.Keyword : effect, cooperative, student team achievement division, learning outcomes